Attribute-based encryption with hidden policies in the access tree - Yan SONG; Zhen HAN; Feng-mei LIU; Lei LIU (Tongxin xuebao)
The existing policies-hidden attribute-based encryption (ABE) schemes could only support a limited access structure,which resulted in weak expressiveness.A new structure of access tree was thus proposed to integrate attribute hiding and secret sharing into “and” gate,“or” gate and “threshold” gate.Then,a tree-based policies-hidden scheme was constructed by using composite order bilinear groups.Under dual system encryption,the scheme was proved to be secure.Furthermore,the analysis and experiment demonstrate that the scheme realize policies-hidden in the complex ac-cess structure without increasing the overhead of computation.As a result,it is more feasible and flexible for applica-tions.